Integrating Local Wisdom into Physics Education Through Traditional Games: A Qualitative Ethnoscience Mapping of Congklak - Tri Hastiti Fiskawarni; Edy Kurniawan; Andi Arie Andriani; Wahyuddin (Ikatan Dosen Sains dan Teknologi Indonesia, 2025)
Physics learning in Indonesia is often experienced as abstract and disconnected from students’ daily cultural lives, which can weaken engagement and make key mechanics ideas harder to grasp. At the same time, many schools face the challenge of keeping local wisdom visible and meaningful within modern, standardized curricula. This study set out to identify physics concepts embedded in the traditional game congklak and to build a clear, classroom-ready mapping that links gameplay events to junior high school mechanics topics while also highlighting character values expressed through play. The research used a qualitative descriptive design with an ethnoscience perspective, combining a focused review of scholarly literature (2015–2025) with three recorded simulated congklak sessions (total 60 minutes) to document observable gameplay phenomena. Literature excerpts and observation logs were coded and synthesized through thematic analysis to develop an auditable concept–value framework. The results show that congklak repeatedly produces mechanics-relevant events that students can easily observe, such as short-range arc-like seed motion during placement, frequent contact interactions between seeds and the board that can be used to discuss interaction and momentum transfer qualitatively, and movement stopping that supports discussion of energy transfer and dissipation. The study also found that congklak naturally embeds local-wisdom values—patience, honesty in counting, fairness in turn-taking, cooperation, and strategic thinking—because these behaviors are required to play by the rules. The novelty of this work lies in providing a transparent workflow that bridges cultural practice and formal physics content while clearly treating gameplay observations as illustrative rather than experimental measurements. Overall, congklak offers a feasible, low-cost, and culturally meaningful way to contextualize introductory mechanics lessons and to open reflective conversations about values, contributing a replicable model for integrating local wisdom into science education.